Cardiogenic shock due to yew poisoning rescued by VA-ECMO: case report and literature review - Nikolaus Schreiber; Martin Manninger; Sascha Pätzold; Alexander C. Reisinger; Stefan Hatzl; Gerald Hackl; Christoph Högenauer; Philipp Eller (Taylor & Francis Group, 2022)
Ingestion of leaves of the European yew tree (Taxus baccata) can result in fatal cardiac arrhythmias and acute cardiogenic shock. This cardiotoxicity derives from taxine alkaloids that block cardiac voltage-gated sodium and calcium channels. Prompt initiation of venoarterial extracorporeal membrane oxygenation is essential to bridge these critically ill patients to recovery, as there is no antidote available. We here report a 39-year old patient with toxic cardiogenic shock after yew poisoning, who was successfully rescued by venoarterial extracorporeal membrane oxygenation and had a full neurological recovery. This report emphasizes the role of intoxications as reversible causes of cardiac arrest and adds further evidence to the body of existing literature thus encouraging the early use of venoarterial extracorporeal membrane oxygenation in patients with yew poisoning and cardiogenic shock.